2020
DOI: 10.3389/fcell.2020.00627
|View full text |Cite
|
Sign up to set email alerts
|

IL-36α Promoted Wound Induced Hair Follicle Neogenesis via Hair Follicle Stem/Progenitor Cell Proliferation

Abstract: Background Wound-induced hair follicle neogenesis (WIHN) is a phenomenon of hair neogenesis that occurs at the center of a scar when the wound area is sufficiently large. Neogenic hair follicles are separated from the pre-existing follicles at the wound edge by a hairless circular region. This WIHN study provides a unique model for developing treatments for hair loss and deciphering the mechanisms underlying organogenesis in adult mammals. Methods The skin of a mouse wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…However, a recent study showed that obesity accelerates hair depletion through IL-1R signaling ( 51 ), likely reflecting a difference in the response to IL-1β in the context of regeneration versus homeostatic maintenance. Similar to our findings, paralog IL-1α has been shown to activate HFSCs and up-regulate IL-36α and IL-6 to promote WIHN ( 26 , 52 , 53 ). Together, the evidence suggests that IL-1 signaling is a powerful proregenerative cue in response to skin damage.…”
Section: Discussionsupporting
confidence: 91%
“…However, a recent study showed that obesity accelerates hair depletion through IL-1R signaling ( 51 ), likely reflecting a difference in the response to IL-1β in the context of regeneration versus homeostatic maintenance. Similar to our findings, paralog IL-1α has been shown to activate HFSCs and up-regulate IL-36α and IL-6 to promote WIHN ( 26 , 52 , 53 ). Together, the evidence suggests that IL-1 signaling is a powerful proregenerative cue in response to skin damage.…”
Section: Discussionsupporting
confidence: 91%
“…In summary, TLR activation in response to wounding leads to IL-6 production and STAT3 phosphorylation, activating a STAT3-dependent gene expression program to promote WIHN. This conclusion agrees with recent studies that have characterized other IL-6 type molecules such as IL-36α that activate STAT3 and induce WIHN (Gong et al, 2020). Strikingly, the same IL-6/STAT3 pathway that governs WIHN is implicated in impaired cutaneous wound healing in aged mice.…”
Section: Dsrna/il-6/stat3/rasupporting
confidence: 92%
“…STAT3 belongs to the signal transduction and transcription activation factor family in cell signal activation and transduction ( Kong et al, 2019 ). It has been shown that STAT3 plays a vital role in the hair follicle and morphogenesis and development ( Sano et al, 2008 ; Yu et al, 2014 ; Nelson et al, 2015 ; Gong et al, 2018 , 2020 ). Whether STAT3 regulates FST is not clear.…”
Section: Resultsmentioning
confidence: 99%